Annual Plan 1998-99 Maharashtra State Part I - Planning Commission (Planning Commission, 1998)
The Annual Plan 1998-99 is the second year of the Ninth Five Year Plan 1997-2002, which shall usher us in the 21st Century. The priorities, as determined by the National Development Council (NDC) in January 1997 for the Ninth Five Year Plan are as under :- Priority to agriculture and rural development with a view to general adequate productive employment and eradication of poverty, Accelerating the growth rate of the economy with stable prices; Ensuring food and nutritional security for all, particularly the vulnerable sections of society; Providing the basic minimum services of safe drinking water, primary health care facilities, universal primary education, shelter, and connectivity to all in a time bound manner; (v) Containing the growth rate of population.
Planning Department Government of Maharashtra